Russian Constructicon - Språkbanken Text (University of Gothenburg, 2024)
A Russian Constructicon

Ett ryskt konstruktikon
Rysk Konstruktikon
Keywords: Language Technology (Computational Linguistics); lexicon; Natural Language Processing; Språkbehandling och datorlingvistik